Health care disparities in megaurban China: the ambivalent role of unregistered practitioners - Bork-Hüffer, Tabea; Kraas, Frauke (Tijdschrift voor economische en sociale geografie, 2015)
One of the unintended effects of China's health care reforms is the emergence of unregistered practitioners. We discuss reasons for their development and their role in the urban health care provision system under consideration of general developments in health care provision and health governance - thereby drawing scientific attention to a by far under-researched topic. We analyse the basic characteristics and strategies of clinic-based unregistered practitioners in Guangzhou and examine their perception and utilisation by rural-to-urban migrants. The research design followed a qualitative dominant mixed methods research approach, which included expert interviews with representatives of administration, indepth interviews with practitioners and migrants, a quantitative survey with 450 migrants and field observations. According to our results, gaps in the formal health care system - especially lack of access of marginalised population groups and inadequate responsiveness - poor enforcement of regulation and corrupt executive personnel are responsible for their emergence and prevalence.